Estudo de um protocolo de otimização para as técnicas radiográficas em radiologia computadorizada - Marcos Eugênio Silva Abrantes (2015)
This work is designed to produce information for the improvement of image quality to deployment in a radiology department based on previous reviews of the images by questionnaires of acceptance and quality e recognition of the parameters used in chest radiographic techniques. The data collected were divided by male, female, PA and LAT thickness, body mass index, biotypes, antropoformic parameters and body evaluation associated with constant voltage and the additional filtration. The results show the predominance of 35 and 40 constants with additional filtration from 0.5 to 1.5 mmAl, voltage in male: (PA and LAT) 86-92 kV and 96-112 kV, female: 85-98 kV and 96-112 kV. The charge applied to the tube for males: (PA and LAT) 5-10 mA.s and 5-16 mA.s, female: (PA and LAT) 6.3-8 mA.s and 9-14 mA.s. Absorbed doses for males: (PA and PF) 0.04-0.17 mGy and 0.03-0.19 mGy and from female (PA and PF) from 0.03-0.22 mGy and 0, 04-0.17 mGy. This procedure can be used in radiology department to implement and acceptance in the quality of images